PSYCHOLOGICAL PRECONDITIONS OF STUDENT’S PLAGIARISM - Olga P. Merkulova; Angelina S. Danilenko (Высшее образование в России, 2016)
In the article we consider the concept of student’s plagiarism and the factors contributing to its prevalence. The results of the empirical study, which has revealed a relationship between the penchant for plagiarism and the indicators of the self-attitude andmotivation for university studies, are presented. It is shown that the most of the students understand the meaning of the word «plagiarism», but at the same time consider situation of plagiarism as acceptable. The article adduces the results of the studies of students’ representations on the prevalence, acceptable and frequency in their own experience the 10 cases of plagiarism. It was revealed that students more inclined to use plagiarism differ by lower level of self-interesting, confidence and communicative motives. It is shown that therecognition of the higher frequency plagiarism in their own learning is also related with lower levels of academic achievement and positive integral self-attitude. More important in psychological terms was identified index of acceptability of plagiarism on representations of students. It is also associated with the lower level of motivation (prestige, creative self-realization, educational and social), self-respect and positive attitude expected from the others.